Religious Diversity in the Digital Economy: Interfaith Legal Pathways to Harmonize Sharia, Christian Ethics, and International Law - Azam, Muhammad; Abdul-Majeed Hamdoun, Abdullah; Alhaleem Maslat Harahsheh , Eid Abed; Mashdurohatun, Anis; Sidauruk, Hamonangan Parsaulian (Contemporary Issues on Interfaith Law and Society, 2025)
The rapid expansion of the digital economy has generated new opportunities for commerce, communication, and innovation, while simultaneously producing complex legal and ethical challenges with profound implications for religious communities in plural societies. Practices such as fraudulent halal certification in online markets, algorithmic bias affecting devotional content, misinformation that exacerbates interreligious tensions, and fintech models that risk violating prohibitions on riba, gharar, and maisir illustrate how digital governance intersects with religious norms and international legal standards. This article examines five key domains in which these interactions are most visible: consumer protection, religious data privacy, online speech and blasphemy-adjacent harms, fintech ethics, and the recognition of cross-border electronic contracts. The study analyzes statutory instruments, international regulatory frameworks, and Sharia jurisprudence alongside Christian and secular legal-ethical perspectives to assess points of convergence and divergence. The findings reveal substantial agreement across traditions on prohibiting fraud, ensuring transparency, and protecting human dignity, alongside persistent tensions regarding religious sensitivities in advertising, content moderation, and financial design. To address these challenges, the article proposes a harmonization roadmap that includes soft-law guidance for digital platforms, faith-sensitive model clauses for e-contracts and online dispute resolution, judicial interpretive canons grounded in maqāṣid al-sharīʿah and international human-rights norms, regulatory sandboxes for ethical fintech innovation, and academic partnerships for training, auditing, and accountability. By situating digital-economy governance within an interfaith legal framework, the article offers a pathway for transforming digital marketplaces into spaces of fairness, inclusivity, and constructive interreligious coexistence, with particular relevance for Muslim-majority contexts such as Indonesia.